Trade openness and environmental quality: International evidence. (May 2016) - Le, Thai-Ha; Chang, Youngho; Park, Donghyun
Abstract: We examine the relationship between trade openness and the environment in a cross-country panel, using the emission of particulate matter (PM10) as the basic indicator of environmental quality. The panel cointegration test results show a long-run relationship between particulate matter emissions, trade openness, and economic growth. We find that increased trade openness leads to environmental degradation for the global sample. However, the results differ according to the income of countries. Trade openness has a benign effect on the environment in high-income countries, but a harmful effect in middle- and low-income countries. These results are generally robust to different measures of trade openness and environmental quality. Interestingly and significantly, the results are consistent with the popular notion that rich countries dump their pollution on poor countries. Finally, we find evidence of a feedback effect between trade openness and particulate matter emissions for the global sample as well as different income groups of countries. Highlights: Relation between trade and the environment is examined for 98 countries. A long-run relationship exists among pollutant emissions, openness, and growth. Openness appears to lead to environmental degradation for the global sample. The relationships differ according to the income of countries. A feedback effect between trade openness and pollutant emissions exists.